Progressive debonding analysis of sandwich composite strips using a cohesive-layerwise spectral finite element model. (15th May 2022) - Siorikis, D.K.; Rekatsinas, C.S.; Chrysochoidis, N.A.; Saravanos, D.A.
Abstract: This paper presents a novel numerical framework for the simulation of debonding growth in sandwich structures via a layerwise spectral finite element model. A variable kinematic layerwise theory is developed, which employs cubic Hermite splines for the composite facesheets and the core and linear interpolation functions for the thin resin-rich layers in connection with continuum damage mechanics for tracking of debonding propagation. The layerwise mechanics and continuum damage mechanics are integrated into a spectral finite element, termed thereafter as cohesive-layerwise spectral finite element, with integration points collocated to nodes and high-order spatial approximation in the plane of the structure. The developed computational model is applied to global mode I, mode II, and mixed-mode fracture problems and correlated with experimental results and reference high-fidelity finite element models. The evaluation cases of the present method reveal significant enhancements in computational speed and meshing process due to elimination of cohesive layer parameter calibration, alleviation of FE aspect ratio constraints and high-convergence rates.